2007
DOI: 10.1074/jbc.m704287200
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Multipotential Mesendodermal Progenitors from Mouse Embryonic Stem Cells via Sustained Wnt Pathway Activation

Abstract: Pluripotent embryonic stem cells (ESCs) are capable of differentiating into cell types belonging to all three germ layers within the body, which makes them an interesting and intense field of research. Inefficient specific differentiation and contamination with unwanted cell types are the major issues in the use of ESCs in regenerative medicine. Lineage-specific progenitors generated from ESCs could be utilized to circumvent the issue. We demonstrate here that sustained activation of the Wnt pathway (using Wnt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 48 publications
(18 reference statements)
3
84
0
1
Order By: Relevance
“…On the other hand, sustained Wnt-signaling activation can induce differentiation of ESC. A recent study showed that long-term treatment of ESCs with Wnt3a protein in the presence of LIF induces differentiation into bipotent mesendodermal cells that produce mesoderm [33]. Similarly to this, we show that depletion of Smek proteins induces mesoderm differentiation.…”
Section: Discussionsupporting
confidence: 59%
“…On the other hand, sustained Wnt-signaling activation can induce differentiation of ESC. A recent study showed that long-term treatment of ESCs with Wnt3a protein in the presence of LIF induces differentiation into bipotent mesendodermal cells that produce mesoderm [33]. Similarly to this, we show that depletion of Smek proteins induces mesoderm differentiation.…”
Section: Discussionsupporting
confidence: 59%
“…By contrast, other studies of modulated Wnt pathway activity in Xenopus and mouse embryos in vivo and in mouse ES cells in vitro have concluded that Wnt signaling promotes mesendodermal differentiation (Bakre et al, 2007;Gadue et al, 2006;Lindsley et al, 2006;Sokol, 1993;Takada et al, 1994). Adding to the confusion, TCF3, a binding partner of -catenin that represses cell differentiation in multiple tissues (Nguyen et al, 2006), has also been proposed to restrict mouse ES cell self-renewal (Cole et al, 2008;Tam et al, 2008;Yi et al, 2008).…”
Section: Introductionmentioning
confidence: 85%
“…Not only does Wnt signaling specify the anteroposterior (AP) body axis in most metazoan animals, but it has also been reported to promote ES cell pluripotency (Nusse et al, 2008;Wend et al, 2010), to specify the mesendodermal lineage and to inhibit neuroectodermal differentiation in mouse ES cells (Aubert et al, 2002;Bakre et al, 2007;Haegele et al, 2003;Lindsley et al, 2006;Sato et al, 2004) and in vertebrate embryos (Yoshikawa et al, 1997;Itoh and Sokol, 1999). Strikingly, whether Wnt ligands and receptors themselves have a proven role in pluripotency continues to be the subject of ongoing debate (Nusse et al, 2008;Wend et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…BMP2 together with Wnt3a constitutes a potent combination of factors to induce the mesoderm (16,17). We thus used the cardiogenic morphogen BMP2 in a defined serum-free medium and in the presence of the FGF receptor inhibitor SU5402 (18).…”
Section: Cardiogenic Commitment Of Pluripotent Stem Cells and Generatmentioning
confidence: 99%